2002
DOI: 10.1088/0953-8984/14/45/101
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional emergence of elastic softening induced by magnetic fields in the unusual heavy-fermion compound PrFe4P12

Abstract: Ultrasonic measurement on the filled skutterudite compound PrFe 4 P 12 exhibits a mysterious temperature dependence of the elastic constant (C 11 -C 12 )/2. Pronounced elastic softening at low temperatures is revived by applying a magnetic field. This fact strongly suggests the 4f-multiplet ground state of the Pr ion split by the crystalline electric field (CEF) to be a 3 non-Kramers doublet. The expectation value of a quadrupole moment with 3 symmetry in the CEF ground state, which leads to elastic softening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…One might speculate about the origin of this deviation due to Kondo effect, reminiscent of the similar behavior observed in PrFe 4 P 12 and PrInAg 2 . [23][24][25] Again, our results show the reasonable agreement with calculation based on the cooperative effect of the CEF and Zeeman effect under external magnetic fields, in particular, above 5 T.…”
Section: Discussionsupporting
confidence: 89%
“…One might speculate about the origin of this deviation due to Kondo effect, reminiscent of the similar behavior observed in PrFe 4 P 12 and PrInAg 2 . [23][24][25] Again, our results show the reasonable agreement with calculation based on the cooperative effect of the CEF and Zeeman effect under external magnetic fields, in particular, above 5 T.…”
Section: Discussionsupporting
confidence: 89%
“…102,103) However, a À 1g -type scalar ordering also causes a sharp anomaly in the elastic constants C 11 À C 12 and C 44 at the transition as discussed in §4.6. Furthermore, the behavior of the elastic constants under a finite magnetic field can also be understood in terms of the scalar order scenario.…”
Section: 103)mentioning
confidence: 94%
“…Ultrasonic measurements 102,103) on PrFe 4 P 12 revealed that the elastic constants C 11 , ðC 11 À C 12 Þ=2, and C 44 show a clear anomaly at T 0 , which becomes larger under a magnetic field. 102,103) The temperature dependence of the elastic constant ðC 11 À C 12 Þ=2 is shown in Fig.…”
Section: Elastic Anomalymentioning
confidence: 99%
“…We take the value for C 3 from experiment, which gives C (0) 11 − C (0) 12 = 70GPa at T = 4.2K, 8 and choose T Q = 0.4K. Then we obtain the values for the combinations B 2 /a Q and B 2 /c ψQ from the fit of the experimental data 16 as Around the phase transition we make series expansion of expressions ( 43) and (44) in terms of (T − T 0 ), and obtain the change δC i j of elastic constants as…”
Section: Case Of Zero Magnetic Fieldmentioning
confidence: 99%